Fabrication of Spaced Concentric Vesicles and Polymerizations in RAFT Dispersion Polymerization - Zhang, Wen-Jian; Hong, Chun-Yan; Pan, Cai-Yuan (Macromolecules, 2014)
Different from concentric vesicles without spacing between the walls, the concentric vesicles with uniform spacing between the walls were rarely fabricated. We successfully fabricate the spaced concentric vesicles (SCVs) via RAFT dispersion polymerization, and continuous propagation of the residual polymer chains inside the large vesicles induces self-assembling to form SCVs. Concentration of the residual polymer chains in the solution of the nascent-formed vesicles is the determining factor for formation of SCVs, and continuous propagation of less or too more residual polymer chains will not form SCVs but form other morphologies. Generally, the concentration of the residual polymer chains after formation of vesicles is too low to self-assemble, so formation of SCVs is impossible. By adjusting the ratio of St/methanol or macro-RAFT agent P4VP-b-PS/P4VP, the concentration of residual polymer chains can be controlled, and further control of the morphologies is achieved. Formation of the inner vesicles by self-assembling inside the large vesicles requires high molecular weight of the polymer chains due to their very low concentration. The polymers of inner vesicles possess very high molecular weight (×106 g/mol) in comparison with the polymer of outmost vesicles (×105 g/mol). Polymerization kinetic study reveals very high increasing rate of the molecular weight inside the vesicles probably owing to long duration of the chain radicals, and the polymerization rate (R p) inside the vesicles is faster than the R p in the outmost vesicles, but both rates are in the same order.